Methods of Arabic Language Learning - Waliyuddin, Waliyuddin; Thamimy, Ardani Ramdhan; Linur, Rahmat (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
implemented in educational settings, including the Direct Method, Natural Method, Grammar-Translation Method, Audiolingual Method, and Suggestopedia. A qualitative approach is employed to evaluate the strengths and weaknesses of each method, as well as their impact on students' language proficiency. The findings reveal that each method possesses unique advantages in enhancing Arabic language skills, with different emphases on aspects such as communication, grammatical understanding, and context of use. The Direct and Natural Methods are found to be effective in improving speaking and listening skills, while the Grammar-Translation Method provides a deeper understanding of language structure. Additionally, Suggestopedia offers an innovative approach through relaxation and motivation techniques. The study concludes that a combination of various methods, tailored to meet students' needs, can create a more comprehensive and effective learning experience in mastering the Arabic language.